Becker’s Nevus Syndrome in a Pediatric Female Patient - Sara Hernandez-Quiceno; Esteban Uribe-Bojanini; Juan Jose Ramírez-Jiménez; Maria Victoria Lopera-Cañaveral; Martin Toro-Ramos; Yuri Usuga-Arcila; Luis Correa-Londoño; Juan Camilo Martinez; Jennifer Monroy; Juan Manuel Alfaro (Case Reports in Pediatrics)
Becker’s nevus syndrome is part of the epidermal nevus syndromes and has been described with a phenotype that includes Becker’s nevus, ipsilateral breast hypoplasia, and variable skeletal malformations. It is more frequent in males than in females (5 : 1) but is more relevant in females. The diagnosis is clinically based and the skin lesion must be present and no other numbered criteria have been established, but with more criteria being present the possibility of the diagnosis is higher. Regarding the treatment of breast hypoplasia, the use of antiandrogen medication has demonstrated adequate clinical response in a dose of 50 mg/day of spironolactone.